The Marketing Potential Of Augmented Reality to Enhance Brand Attitude - Abdan A. Kuncoro; Maria Apsari Sugiat; Muslim Amin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this study is to examine the impact of Augmented Reality (AR) application usage at IT Telkom Purwokerto on consumer brand attitudes. A total of 200 questionnaires were distributed, with 125 deemed suitable for analysis. The findings reveal that the use of the AR application significantly influences consumer attitudes towards the brand, particularly in terms of user experience, engagement, and perceived realism. The quality of the AR application is shown to have good reliability, and each dimension positively correlates with consumer attitudes. The perceived realism of the AR experience is a crucial factor in shaping positive consumer attitudes towards the brand. The study also identifies a significant relationship between AR application usage, consumer satisfaction, and brand loyalty. Practically, AR can aid IT Telkom Purwokerto in developing more effective marketing models. This study proposes a model to understand the effect of AR applications on positive consumer brand attitudes, assisting marketers in implementing more effective marketing strategies.